Comparison of latent typologies of posttraumatic stress disorder and depression symptoms across military personnel from India and the US. (March 2020) - Contractor, Ateka A.; Weiss, Nicole H.; Schick, Melissa R.; Natesan Batley, Prathiba; Forkus, Shannon R.; Sharma, Rachita
Highlights: We examined and compared PTSD-depression typologies across India and U.S. veterans. Optimal 4-class solution differed in severity and severity/type in India and U.S. samples respectively. Across cultural samples, classes were similar in number but different in meaning/nature. Anxiety, number of traumas, and resilience predicted class membership in India sample. Alcohol use and rumination predicted class membership in U.S. sample. Abstract: Research has identified heterogeneous subgroups of individuals based on posttraumatic stress disorder (PTSD) and depression symptoms. Using data collected from military personnel in India ( N = 146) and U.S. ( N = 194), we examined (1) the best-fitting latent class solution; (2) multi-group invariance of the class solution; and (3) construct validity of optimal class solution. Results indicated that the optimal 4-class solution differed in severity and severity/type in the India and U.S. samples respectively. With similarity in the optimal number of classes across cultural samples, the meaning/nature of classes differed. In the India sample, anxiety severity predicted the Low Severity Class vs. all other classes, and the Moderately High Severity/High Severity Classes vs. the Moderately Low Severity Class; number of traumas predicted the High Severity Class vs. other classes; and resilience predicted the Moderately Low Severity Class vs. the Moderately High Severity Class. In the U.S. sample, alcohol use predicted the High Severity Class vs. all other classes, and the High Depression-Low PTSD Class vs. the Low Severity Class; rumination significantly predicted the High Severity and High Depression-Low PTSD Classes vs. each of the High PTSD-Low Depression and Low Severity Classes. Thus, meaning and nature of PTSD-depression subgroups may vary culturally; hence, culturally-sensitive interventions need to account for this heterogeneity.